2019
DOI: 10.1590/0001-3765201920180994
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of U87MG human glioblastoma cells by Usnea longissima Ach.

Abstract: Herbal medicines are efficient to reduce side effects in the fight against glioblastoma, which plays a critical role within brain cancer species. The recent studies designated for testing the effects of lichens that have shown numerous anticancer activities on glioblastoma so far. In the present study, different concentrations of water extract obtained from Usnea longissima Ach. were used in order to determine cytotoxic (via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and lactate dehydrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Lichens contain diverse species and exhibit multiple functions such as in traditional medicine, and the preparation of food, perfume, and dye [ 32 ]. Recently, the cell killing effect of lichen extracts has received attention in the treatment of several types of cancer as shown by several studies [ 11 , 12 , 13 ] except for oral cancer. In the current study, we investigated the anticancer effect and mechanism of MEUB against oral cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lichens contain diverse species and exhibit multiple functions such as in traditional medicine, and the preparation of food, perfume, and dye [ 32 ]. Recently, the cell killing effect of lichen extracts has received attention in the treatment of several types of cancer as shown by several studies [ 11 , 12 , 13 ] except for oral cancer. In the current study, we investigated the anticancer effect and mechanism of MEUB against oral cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, water extract of U. longissima Ach. exhibits growth inhibition of human glioblastoma GBM U87MG cells but it shows less damage to primary mixed glial-neuronal (PMGN) non-cancer cells [ 12 ], suggesting a preferential killing effect on human glioblastoma cells. The preferential killing ability of extracts from other Usnea species were also reported from animal model study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Yiqi Huayu Jiedu decoction, which comprises various Chinese herbs and natural compounds, was reported to increase the anti-cancer effects of standard chemotherapy in patients with stage III gastric cancer after radical gastrectomy and improve the quality of life of patients [10]. In addition to these reports, several reviews and in vivo and in vitro studies have demonstrated that a variety of natural products possess anti-cancer potential and can avoid the undesirable effects of standard therapies of malignancies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%